Fieldwork in South Asia : Memories, Moments, and Experiences. - Chaudhuri, S. K. (Sarit Kumar); Chaudhuri, Sucheta Sen, 1963- (SAGE Publications, 2014)
Fieldwork in South Asia is a valuable attempt to listen and learn from the memories and significant moments of fieldwork done by anthropologists, sociologists, and even historians from South Asia. The essays lead towards a deeper understanding of concerns of fieldwork located in various field sites across South Asia without assuming or applying fixed normative rules for the whole region. In the process, the volume allows the reader to have an option to locate or relocate ethnographic or other forms of texts in the context of growing methodological contours and dilemmas in the social science. Ab.